2003
DOI: 10.1080/10640260390167447
|View full text |Cite
|
Sign up to set email alerts
|

Dental Practitioners and Eating Disorders

Abstract: To better understand how dental practitioners identify, counsel, and refer patients with eating disorders. A questionnaire was mailed to 625 dental practitioners, 54 (19%) of the dentists and 69 (20%) of the dental hygienists responded. Most dental practitioners were aware of eating disorder patients in their practices and most discussed their findings with their patients or parents. However, one of the suggestions most commonly given to patients, to brush immediately after vomiting, may be counter therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The mean age at onset of EDs in the study group was 16 (range, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] yr and the mean duration of the disease was 4.4 (range, 0.3-35) yr. Sixty-one per cent (n = 33) of patients had had an ED for more than 1 year. Almost half of the ED patients (n = 25) reported that they had induced vomiting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age at onset of EDs in the study group was 16 (range, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] yr and the mean duration of the disease was 4.4 (range, 0.3-35) yr. Sixty-one per cent (n = 33) of patients had had an ED for more than 1 year. Almost half of the ED patients (n = 25) reported that they had induced vomiting.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, only a few dentists inform patients/parents about their suspicion of EDs, and dentists report insufficient knowledge of EDs (16). Consequently, an increased knowledge of EDs and their effect on oral health is likely to increase the probability of intervention by the dentist, which, in turn, could be of great value regarding early detection and intervention in patients with EDs (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dental fear is common in persons with EDs , a condition that further complicates interaction with the dentist. This is confirmed in the literature, where dentists express different levels of difficulty when communicating about EDs with patients who the dentist suspects of having an ED . On the other hand, the literature on how persons with EDs experience dental visits is, to our knowledge, very sparse.…”
mentioning
confidence: 76%
“…5,36 It is interesting to consider that TE tends to be found on plaque-free tooth surfaces, although the presence of plaque is an essential factor for the progression of DC. 37,38 As a result, it still remains unclear whether DC and dental erosion are related and this might be an explanation to the literature lack of consensus referring to the association of both conditions and EDs.…”
Section: Discussionmentioning
confidence: 99%